PEMBANGUNAN KEBUN BIOLOGI WAMENA - M Rahmansyah; HJD Latupapua (Research Center for Biology-Indonesian Institute of Sciences, 2003)
The richness of biological resources (biodiversity) in mountainous area of Papua is an asset that has to be preserved.Exploitation of natural resources often cause damage on those biological assets and as genetic resources.Care has to be taken to overcome the situation of biological degradation, and alternate steps had been shaped on ex-situ biological conservation. Wamena Biological Gardens, as an ex-situ biological conservation, has been established to keep the high mountain biological and its genetic resources in Papua.